2004
DOI: 10.1177/1074840703261065
|View full text |Cite
|
Sign up to set email alerts
|

Social Role Experiences of Women Living with Rheumatoid Arthritis

Abstract: This study was designed as the qualitative arm of a larger quantitative study (N = 156) of the relationships among social role quality, physical health, and psychological well-being of women living with rheumatoid arthritis (RA). A subset of 20 midlife and late-life women from this larger sample participated in semistructured interviews with the specific aims of investigating how fulfilling they found social roles to be, including their spouse, mother, worker, and homemaker roles, while contending with RA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 29 publications
(25 reference statements)
2
37
0
1
Order By: Relevance
“…., awkward [and] ugly'' [35]. Given the unpredictable nature of the symptoms of RA, this ''social inadequacy'' [36] was seen to impose ''periodic emotional burdens'' and restrictions [37] ''permeating every sphere of life'' [33]. People with RA lost their independence and did not relish dependency.…”
Section: Results: Second Synthesis: the Nature Of Symptoms And Stratementioning
confidence: 97%
See 2 more Smart Citations
“…., awkward [and] ugly'' [35]. Given the unpredictable nature of the symptoms of RA, this ''social inadequacy'' [36] was seen to impose ''periodic emotional burdens'' and restrictions [37] ''permeating every sphere of life'' [33]. People with RA lost their independence and did not relish dependency.…”
Section: Results: Second Synthesis: the Nature Of Symptoms And Stratementioning
confidence: 97%
“…''Choose to leave things undone'' (p. 383). ''It's what's best for your illness and that's the driving force behind most decisions'' (p. 385) [43] ''To make the best of a bad situation'' (p. 661) [30] Use of time (pacing, planning, prioritization) [48] ''Trying to 'get on with things''' (p. 1578) [44] Body management (''You can fight it''); Mind management (''I can't do that''); Mind-body management (''Don't live against it, live with it''); Pacing (p. 1046) [35] ''They learned to live with [it]'' (p. 42); Conserve energy (p. 42); Transformation [36] ''I get through the day. I don't have anything else to give'' (p. 39) Unburdening of social role obligations (p. 43) [40] ''I have almost learned to live with it'' (p. 109) [33] Pacing; re-prioritizing activities (p. 701) …”
Section: Results: Second Synthesis: Perceptions Of Controlmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the variation in the level of pain and ability from one period to another and the unpredictability of the progression of the disease affect their planning concerning their future occupations (26). These changes relate to how people's occupations influence their interactions and relations with others (27). Thus, this literature review of individuals with RA has revealed that existing research has concentrated on which occupations they engage in or in which their engagement is restricted.…”
Section: Introductionmentioning
confidence: 97%
“…RA is a chronic infl ammatory disease, mainly affecting peripheral joints (Arnett et al, 1988), and is characterized by periods of exacerbation and remission (Plach et al, 2004). RA attacks all age groups and is three times more common in women than in men (Symmons et al, 2002).…”
Section: Introductionmentioning
confidence: 99%